Mechanical Performance of Jute and Basalt Fiber Geo-grid-Reinforced Epoxy Hybrid Composite Material - Lalta Prasad; Aruna Saini; Virendra Kumar (Journal of Natural Fibers, 2021)
In the present work, the jute fiber and basalt fiber mats (geo-grid) reinforced with epoxy hybrid composite material were prepared in a laboratory by using hand layup technique. The influence of the stacking sequence on physico-mechanical properties of hybrid composite materials was experimentally investigated as per the ASTM standards. The moisture content in the hybrid composite was slightly on higher side as compared to the simple composite (six layers of jute). The tensile strength of the hybrid composite (two layers of jute) was enhanced by 20% as compared to the simple composite. It was observed that the hybrid composite shows high strain (4.5%) and large extension (13.5 mm) in the flexural test as compared to that of simple composite.